Physiological effects of in ovo delivery of bioactive substances in broiler chickens - Kpodo, Kouassi R.; Proszkowiec-Weglarz, Monika (Frontiers in Veterinary Science, 2023)
The poultry industry has improved genetics, nutrition, and management practices, resulting in fast-growing chickens; however, disturbances during embryonic development may affect the entire production cycle and cause irreversible losses to broiler chicken producers. The most crucial time in the chicks' development appears to be the perinatal period, which encompasses the last few days of pre-hatch and the first few days of post-hatch. During this critical period, intestinal development occurs rapidly, and the chicks undergo a metabolic and physiological shift from the utilization of egg nutrients to exogenous feed. However, the nutrient reserve of the egg yolk may not be enough to sustain the late stage of embryonic development and provide energy for the hatching process. In addition, modern hatchery practices cause a delay in access to feed immediately post-hatch, and this can potentially affect the intestinal microbiome, health, development, and growth of the chickens. Development of the in ovo technology allowing for the delivery of bioactive substances into chicken embryos during their development represents a way to accommodate the perinatal period, late embryo development, and post-hatch growth. Many bioactive substances have been delivered through the in ovo technology, including carbohydrates, amino acids, hormones, prebiotics, probiotics and synbiotics, antibodies, immunostimulants, minerals, and microorganisms with a variety of physiological effects. In this review, we focused on the physiological effects of the in ovo delivery of these substances, including their effects on embryo development, gastrointestinal tract function and health, nutrient digestion, immune system development and function, bone development, overall growth performance, muscle development and meat quality, gastrointestinal tract microbiota development, heat stress response, pathogens exclusion, and birds metabolism, as well as transcriptome and proteome. We believe that this method is widely underestimated and underused by the poultry industry.